Identification of Parameters of the Hydrostatic Model of the Working Equipment Drive System of a Wheel Loader to Study the Effectiveness of the Energy Recovery System - Cezary RUDZKI; Cezary RUDZKI (Identyfikacja parametrów modelu hydrostatycznego układu napędu osprzętu roboczego ładowarki kołowej, na potrzeby badań efektywności układu rekuperacji energii, 2024)
Research conducted on hybrid drive systems of working machines is quite often limited to simulation studies, omitting the experimental determination of the parameters of a real machine. The article describes the course and results of experimental identification studies, which, in the further part of broader research, will be used to validate the hydrostatic model of the wheel loader drive system, which will be used to research the effectiveness of the energy recovery system. After defining the machine and identifying the structure and components of its drive system, the parameters that were determined during the research were determined. The identification tests were divided into two groups. The first of them was aimed at determining the operating parameters of the real object under different operating conditions, while the second one enabled the determination of dynamic parameters in response to impulse forcing. Based on the measurements, the time courses of the measured quantities and all assumed parameters were determined.
Keywords: Efektywność układu rekuperacji energii; Efektywność układu rekuperacji energii